Analisis Harga Pokok Produksi sebagai Dasar Penetapan Harga Jual pada Usaha Fashion Lokal Voraya Wear - Na’ilah Syakirah Febriana; Lintang Pramudhita; Dinda Septiana; Sara Imelda Susanti; Fitri Komariyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Local fashion businesses require accurate production cost calculations to ensure appropriate and sustainable pricing decisions. Problems often faced by small businesses is determining selling prices without comprehensive calculation of the cost of production. This study aims to analyze the calculation of the cost of production as the basis for determining the selling price at Voraya Wear, a student-based local fashion business developed through the Student Creativity Program (PKM). The research used a descriptive quantitative approach with direct practice methods. Data were collected through observation, documentation, and financial records, then analyzed using the full costing method to calculate the cost of production and the cost-plus pricing method to determine the selling price. The results show that the total production cost was Rp1,831,064 for 24 units, resulting in a unit cost of Rp65,757 for shirts and Rp86,832 for pants. By applying a profit margin of 30–40%, the business generated total revenue of Rp2,520,000 and a net profit of Rp688,936. These findings indicate that accurate cost calculation supports rational pricing decisions and ensures business profitability and sustainability.